2020
DOI: 10.1186/s12960-020-0446-5
|View full text |Cite
|
Sign up to set email alerts
|

Nurse staffing in large general hospitals in China: an observational study

Abstract: Background: The appropriate staffing of nurses not only reflects the situation of nursing management of human resource, but also is related to the nursing quality in hospitals. This study investigated the staffing of nurses in large general hospitals in China. Methods: In this study, a database established by the National Centre for Nursing Care Quality Control, which conducted a national survey of the staffing of nurses in China mainland in 2017, was analysed. The time-point survey data of 20 375 departments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 18 publications
2
29
0
1
Order By: Relevance
“…According to the health workers in this study, integration of traditional midwives during pandemics such as COVID-19 and other crises is necessary. This recommendation from the health workers concurs with findings from a recent study in Kenya by Kimani et al (2020) , who argued that integrating community health workers by expanding existing midwifery centers and creating new ones run by qualified midwives (“skilled birth attendants”) that are closer to or in rural communities could be a viable long-term plan that can reduce the burden on hospitals, and minimize infections and maternal deaths during pandemics such as COVID-19.…”
Section: Discussion and Analysis: Making Tough Choices That Leave Womsupporting
confidence: 78%
See 1 more Smart Citation
“…According to the health workers in this study, integration of traditional midwives during pandemics such as COVID-19 and other crises is necessary. This recommendation from the health workers concurs with findings from a recent study in Kenya by Kimani et al (2020) , who argued that integrating community health workers by expanding existing midwifery centers and creating new ones run by qualified midwives (“skilled birth attendants”) that are closer to or in rural communities could be a viable long-term plan that can reduce the burden on hospitals, and minimize infections and maternal deaths during pandemics such as COVID-19.…”
Section: Discussion and Analysis: Making Tough Choices That Leave Womsupporting
confidence: 78%
“…This concurs with recent findings from other studies that also report an increase in maternal deaths globally due to COVID-19 ( Hussein, 2020 ; Takemoto et al, 2020 ). Supporting my own findings, Kimani et al (2020) also noted for Nairobi, Kenya that fear of contracting COVID-19 likely kept many women from attending reproductive health services. Relatedly, Delamou et al (2017) showed that fear of infection at health facilities was also reported by women in Guinea during the recent Ebola epidemic there (see also Strong and Schwartz 2016 ).…”
Section: Discussion and Analysis: Making Tough Choices That Leave Womsupporting
confidence: 72%
“…Both existing nurses and nal year nursing students who will soon be on the job market are important human resources for health in the long term. There has been a greater demand from health institutions for nurses, especially for nurses with higher educational levels [33],Judging from the growth rate of nurses in the past 10 years, the importance of nurse supplement has attracted the attention of the national government in China [34].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 300 hospital nurses across nine European countries revealed that MNC and understaffing significantly increased the 30‐day mortality rate and post‐surgical admissions (Ball et al., 2018). In China, nurse staffing is improving, but the shortage of nurses remains the primary concern (Shen et al., 2020). Indeed, inadequate staffing was the most commonly cited significant contributor to MNC (Griffiths et al., 2018).…”
Section: Introductionmentioning
confidence: 99%